Exosomal miRNA Profiling is a Potential Screening Route for Non-Functional Pituitary Adenoma - Lyu, Liang; Li, Haiyan; Chen, Cheng; Yu, Yang; Wang, Li; Yin, Senlin; Hu, Yu; Jiang, Shu; Ye, Feng; Zhou, Peizhi (Frontiers in Cell and Developmental Biology, 2022)
Non-functional pituitary adenomas (NFPAs) are one of the most prevalent pituitary adenoma subtypes. The lack of reliable screening approach for NFPAs for the insidious clinical course usually leads to delays in medical therapy and consequently worse prognosis. Hence, we employed a sequence cohort (patient: control, 6:2) and a validation cohort (patient: control, 22:8) to develop a serum exosomal miRNA profile-based method for NFPA screening and prognosis prediction. We found that a total of 1395 kinds of human miRNA were detected. Compared with healthy donors, 18 up-regulated and 36 down-regulated miRNAs showed significantly alteration in expression in NFPA patients. Target genes of differentially expressed miRNAs are mainly in axonogenesis and cancer-associated terms in enrichment analysis. After validation, hsa-miR-486-5p, hsa-miR-151a-5p, hsa-miR-652-3p_R+1 and hsa-miR-1180-3p were promising biomarkers for NFPA, in which miR-486-5p was the most competent one. After a median of 33 months of prospective follow-up, exosomal hsa-miR-486-5p also was an efficient predictive biomarker for progression or relapse of NFPAs. By protein-protein interaction network construction of hsa-miR-486-5p targeted genes, the core modules revealed a high possibility that exosomal hsa-miR-486-5p regulated tumor progression by epigenetic regulation of MAPK signaling pathways. In conclusion, exosomal hsa-miR-486-5p, hsa-miR-151a-5p, hsa-miR-652-3p_R+1 and hsa-miR-1180-3p are candidate biomarkers for diagnosis and screening of NFPAs. More importantly, prospective follow-up reveals that hsa-miR-486-5p can be regarded as a significant predictor for prognosis of NFPAs.